Department of Environment and Coastal Resources - (:unkn) unknown (My University, 2011)
MISSION To ensure sustainable utilization of the natural resources of the Turks and Caicos Islands, protect and promote biodiversity and economic prosperity through a sustainable fishing industry and a protected areas system.
Keywords: Environment and Coastal Resources